Anti-inflammatory and analgesic effects of methanol extract of stellaria media (L.) Vill leaf (2012)
The anti-inflammatory and analgesic effect of the methanolic extract of Stellaria media (L.) Vill leaf was studied using albumen-induced paw oedema and formalin-induced paw lick in rats as the anti-inflammatory test models; acetic acid-induced writhing, hot plate and tail flick tests in mice as the analgesic models. Three groups of five rats or mice each were administered orally with the leaf extract of S. media at 100mg/kg, 300mg/kg or 500mg/kg body weight respectively. A fourth group was administered with Indomethacin (5mg/kg b.w) and distilled water (10mls/kg b.w) for the control group. The extract of S. media dose-dependently, significantly (p<0.05) inhibited egg albumen-induced paw oedema as effectively as Indomethacin. The late phase of the formalin response was also inhibited. The extract at 300mg/kg body weight produced a significant (p<0.05) inhibition of the acetic acid-induced abdominal constrictions in mice compared to the control group and mice administered with indomethacin. The analgesic property of the extract was also exhibited in the tail flick test as the extract significantly (p<0.05) increased the tolerance of the mice to pain relative to indomethacin-treated mice. The methanolic extract of S. media showed potent peripherally and centrally mediated anti-inflammatory and analgesic properties. The analgesic effect appears mediated through inhibition of release of histamine, serotonin and kinins, prostaglandin, cyclooxygenase and slow reacting substance.